2018
DOI: 10.3400/avd.ra.18-00064
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Embolization of Inferior Mesenteric Artery to Prevent Type II Endoleak Following Endovascular Aneurysm Repair: A Review of the Literature

Abstract: Type II endoleak is a common complication that develops after endovascular aneurysm repair. Patients with type II endoleak, which has persisted for 6 months, have a significantly higher rate of aneurysmal sac enlargement, reintervention, and rupture. To date, several studies have examined the effectiveness of preoperative embolization of branch vessels for the prevention of type II endoleak. Particularly, the embolization of the large inferior mesenteric artery (IMA) seems to be a precise, safe, and effective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Current guidelines suggest that a conservative approach is appropriate for isolated type II endoleaks without sac expansion [24,25]. Intervention is recommended when there is a sac enlargement of more than 10 mm [24,25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current guidelines suggest that a conservative approach is appropriate for isolated type II endoleaks without sac expansion [24,25]. Intervention is recommended when there is a sac enlargement of more than 10 mm [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…In this series, most type II endoleaks resolved spontaneously, and only 3 patients required intervention. Nevertheless, secondary interventions for type II endoleaks are often unsatisfactory as recurrence is common, and long-term follow-up is also mandatory [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Muthu et al [37] in a study performed in 2007 where patients that received IMA embolisation combined with intraprocedural thrombin injection in 69 consecutive patients that underwent elective EVAR showed a trend of endoleak reduction; however, no statistically significant difference was reached (26% compared with 14%) and the authors concluded that ongoing research into means to prevent lumbar endoleaks is required. Even though there is a variety of studies available, there is still not enough evidence to support routine embolisation of the IMA or the lumbar arteries or intraprocedural thrombin injection prior to routine EVAR and this remains an operator’s preference [38].…”
Section: Type II Endoleaksmentioning
confidence: 99%
“… 29 ) We are currently conducting an RCT (UMIN000022147) to target type II EL high-risk cases with one of the above 3 risk factors and aim to determine whether IMA embolization during EVAR can inhibit type II EL. 29 ) If a few slight adjustments are made, operative time, irradiation time, and contrast medium volume for IMA embolization during EVAR could be comparable with cases which do not undergo embolization, which is acceptable as an option during EVAR. 30 ) We plan to discuss the utility of this procedure following the conclusion of the ongoing RCT.…”
Section: Long-term Outcomes Of Evar and Issues For Improvementmentioning
confidence: 99%